Binding characteristics of the ovine membrane progesterone receptor alpha and expression of the receptor during the estrous cycle - Nett Terry M; Arreguin-Arevalo J Alejandro; Ashley Ryan L (BMC, 2009)
Abstract Background Classically, progesterone has been thought to act only through the well-known genomic pathway involving hormone binding to nuclear receptors and subsequent modulation of gene expression. However, there is increasing evidence for rapid, non-genomic effects of progesterone in a variety of mammalian tissues and it is possible that a membrane PR (mPR) is causing these events. We recently isolated and characterized an ovine mPR referred to as mPR-alpha, distinct from the nuclear PR. Based on predicted structural analysis, the ovine mPR-alpha possesses seven transmembrane domains typical of G protein-coupled receptors. Despite the homology to other reported mPRs, information pertaining to the steroid binding characteristics of the ovine mPR-alpha was lacking. Additionally, the ovine mPR-alpha transcript has been identified in the hypothalamus, pituitary, uterus, ovary and corpus luteum, yet changes in expression of the ovine mPR-alpha in these tissues were not known. Consequently, the purpose of this work was to determine the steroid binding characteristics of the ovine mPR-alpha and to investigate possible changes in expression of the ovine mPR-alpha in reproductive tissues throughout the estrous cycle. Methods Binding studies were performed using crude membrane fractions from CHO cells expressing the mPR-alpha. Using quantitative Real-time PCR we determined the expression pattern of mRNA for the ovine mPR-alpha during the ovine estrous cycle in tissues known to express the mPR-alpha. Jugular blood samples were also collected and analyzed for serum concentrations of P4 to ensure ewes were at the appropriate stage of their cycle. Results Only progesterone, 20alpha-hydroxyprogesterone and 17alpha-hydroxyprogesterone were able to displace binding of 3H-P4 (P < 0.001) to membrane fractions from CHO cells expressing ovine mPR-alpha. The average B-max and Kd values for three separate experiments were 624 +/- 119 fmol/micro gram protein and 122 +/- 50 nM, respectively. Significant changes in expression of mRNA for the mPR-alpha during the estrous cycle were noted in the corpus luteum and uterus. Conclusion The mPR-alpha specifically binds progestins and its expression was correlated to progesterone secretion during the ovine estrous cycle. Results from the present studies suggest that mPR-alpha may have an important physiological role during the ovine estrous cycle.